The Dual-Tone Electric Talempong Using Piezoelectric Based on Teensy 4.1 - Annisa Aulia Army; Asrizal Asrizal; Mairizwan Mairizwan; Indra Yuda; Mohd Effindi Samsuddin (RESSTECH, 2024)
The Minangkabau tribe has a traditional percussion instrument called Talempong. Talempong is one of the cultural heritages that is rarely used by today's young generation. Due to the expensive price of Talempong, the size of the Talempong base reaches 140x35 cm, heavy enough that 2-3 people are needed to lift it. Therefore, this research aims to create and design a dual tone electric Talempong system using piezoelectric sensors based on teensy 4.1 as a new innovation for traditional Talempong that is lighter, and minimalist. This research method is engineering research that explains the performance specifications that explain the performance of the electric Talempong system and the design specifications explain the accuracy and precision of the electric Talempong sound. Based on the objectives of the research, the results of the performance specifications of the tool were obtained, namely the characterisation of piezoelectric sensors, signal control circuits, Talempong sound recordings, and Talempong elektik mechanics. While the results of the design specifications are the results of the analysis of the average accuracy of the original Talempong sound with the electric Talempong getting accuracy data of 99.8%. The average error in the frequency accuracy data of the original Talempong with the electric Talempong is 0.24%. The accuracy data obtained for tone C is 99.9%, tone G 99.9%, and tone C ‘observance at 100%. The average practicalisation data for electric talempog musical instruments is 94% with very practical criteria.